The multilevel correlates, contributions, and consequences of leader humility in humanitarian aid work - Davis, Edward B.; Barneche, Kelly; Aten, Jamie D.; Shannonhouse, Laura R.; Wang, David C.; Van Tongeren, Daryl R.; Davis, Don E.; Hook, Joshua N.; Chen, Zhuo Job; Lefevor, G. Tyler; McElroy-Heltzel, Stacey E.; Elick, Emilie L.; et al. (Frontiers in Psychology, 2023)
Objective Leader humility has been linked to many positive outcomes but not examined in humanitarian aid work. Three studies examined the multilevel correlates, contributions, and consequences of leader humility in Medair—a large, multinational, faith-based aid organization. Study 1 examined correlates of leader humility in a sample of 308 workers and 167 leaders. Study 2 explored multilevel contributions of leader humility in 96 teams comprised of 189 workers. Study 3 utilized a subsample (50 workers, 34 leaders) to explore consequences of Time 1 leader and team humility on outcomes 6 months later. Method Participants completed measures of humility (general, relational, team), leader and team attributions (e.g., effectiveness, cohesion, and growth-mindedness), organizational outcomes (e.g., job engagement and satisfaction; worker and team performance), and psychological outcomes (e.g., depression, anxiety, compassion satisfaction, and flourishing). Results Leader and team humility contributed to multilevel positive attributions about leaders (as effective and impactful), teams (as cohesive, psychologically safe, and growth-minded), and oneself (as humble), and those attributions contributed to organizational and psychological outcomes. Teams’ shared attributions of their leader’s humility contributed to higher worker job satisfaction and team performance. Longitudinally, for workers and leaders, leader and team humility were associated with some positive organizational and psychological outcomes over time. Conclusion In humanitarian organizations, leader humility seems to act as an attributional and motivational social contagion that affects aid personnel’s positive attributions about their leaders, teams, and themselves. In turn, these multilevel positive attributions contribute to several positive team, organizational, and psychological outcomes among workers and leaders.